2022
DOI: 10.3390/jcm11051432
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the Immune Microenvironment in the Spontaneous Regression of Cervical Squamous Intraepithelial Lesions (cSIL) and Implications for Immunotherapy

Abstract: Cervical high-grade squamous intraepithelial lesions (cHSILs) develop as a result of a persistent high-risk human papilloma virus (hrHPV) infection. The natural course of cHSIL is hard to predict, depending on a multitude of viral, clinical, and immunological factors. Local immunity is pivotal in the pathogenesis, spontaneous regression, and progression of cervical dysplasia; however, the underlying mechanisms are unknown. The aim of this review is to outline the changes in the immune microenvironment in spont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 165 publications
1
7
0
Order By: Relevance
“…Literature data support the hypothesis that 80% of HR-HPV infections spontaneously clear within 18 months thanks to the host’s immune system [ 37 , 38 , 39 , 40 ]. The persistent infection (around 10%) develops an LSIL/CIN1 lesion, and its progression to HSIL/CIN2+ is sustained by a failure in the immune system.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Literature data support the hypothesis that 80% of HR-HPV infections spontaneously clear within 18 months thanks to the host’s immune system [ 37 , 38 , 39 , 40 ]. The persistent infection (around 10%) develops an LSIL/CIN1 lesion, and its progression to HSIL/CIN2+ is sustained by a failure in the immune system.…”
Section: Discussionmentioning
confidence: 71%
“…The persistent infection (around 10%) develops an LSIL/CIN1 lesion, and its progression to HSIL/CIN2+ is sustained by a failure in the immune system. In fact, the pro-inflammatory HPV-specific immune response constitutes the base of the clearance of HPV in healthy women [ 40 ]. A previous study found that in low-grade CIN HPV-16-related, systematic T-cell response to HPV E2 protein was associated with lesion regression, whereas the T-cell response to HPV 16 E6 protein was associated with lesion progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In CC, a compromised microenvironment is mainly a consequence of deconstructed constituent parts of the vaginal microenvironment [ 26 , 27 ]. The intrinsic problems recall the simultaneous presence of multiple factors, such as the high inflammatory state, the presence of SNPs on genes that regulate the expression of immunosuppressive cytokines and interleukins, and a persistent local dysbiosis; these, in turn, facilitate the long-term aggressiveness of the HPV and Chlamydia infection [ 19 , 28 ].…”
Section: The Immune Profile Of the CC Microenvironment C Tr...mentioning
confidence: 99%
“…HPV infections are common in sexually active women, and most are transient infections that are cleared within months to 2 years after acquisition, without any clinical symptoms or signs 2 . However, persistent HR‐HPV infections develop in approximately 10% of infected women and are associated with the development of cervical premalignant lesions and their subsequent progression into invasive cervical cancer 3 . The host's immune system contains both innate and adaptive immune responses that are critical for successful defense against HPV infection.…”
Section: Introductionmentioning
confidence: 99%